Assessment of the Sta. Ana Medical Records Department in quality records management. - Padilla, Grace H.
The medical records division of a hospital is integral to the proper function of its institution. The aim of this study is to assess the quality of medical records management of Sta Ana Hospital (SAH), a tertiary government hospital, and to identify existing gaps specifically in terms of compliance with existing standards, adequacy of workforce, medical record keeping and physical facilities. This is a cross-sectional descriptive study done through: comparing the hospital's manual with local and international standards; comparison of focus group discussion (perceived) with observed (actual) time and motion on personnel's tasks; workload indicator staffing need (WISN) calculation; appraisal of charts and calculation of required storage space. Results showed SAH manual compliance with the DOH (93%), PhilHealth (94%) and JCAH (80%). SAH medical record department has a well written vision, mission and objectives. The Medical Records Committee is inactive. Workforce is inadequate with FGD WISN ratio of 7:24(29%) of the required staff and WISN ratio of Observed actual time and motion of 7:13 (53%) of the required staff. Systematic random sampling (n=107) of charts showed eighty-two (82%) percent were incomplete particularly the clinical forms that lack weight (93%) and vital signs (3%). Fifty-one percent (51%) were inaccurate mainly due to indefinite diagnosis (48%) and vague (27%) patient history. These are responsibilities of the medical personnel. The storage space available is 79% of the required storage and by 2015, it is computed to be only 60% of the required. In conclusion, the Sta Ana Hospital Medical Records Department is generally compliant with the existing standards with some areas identified for improvement specifically in the quality of the medical records, inadequate manpower and insufficient physical structure for future storage. Activation of Medical Records Committee is essential to ensure quality of records management in Sta Ana Hospital.
Management study (MHA)--University of the Philippines Manila, 2013
Keywords: Medical records